Arranjos institucionais e políticas públicas: o caso do plano de expansão da Rede Federal de Educação Profissional Científica e Tecnológica - Souza, Raquel Eugenio de (2021)
The research aimed to evaluate the Expansion Plan of the Federal Network of Scientific and Technological Professional Education (RFEPCT),as a public policy, from the perspective of the dimensions of institutional arrangements, that emerge as an innovation in the way of promoting the formulation and implementation of public policies. The study is justified, as a theoretical contribution, as it addresses the theme of professional education in Brazil, and the expansion policy of the RFEPCT, which promoted the interiorization of the federal network, the encouraging regional development, and access to professional training for citizens in different regions of Brazil. To meet the objectives of the study, it was decided to carry out a qualitative, descriptive and explanatory research, through the case study of the RFEPCT Expansion Plan, and for conducting bibliographic and documentary research. Specifically, it sought to: discuss public policies and institutional arrangements; understand the relevance of institutional arrangements in the evaluation of public policies for regional development, characterize the RFEPCT Expansion Plan in its historical, political, socioeconomic and institutional contexts; identify the forms of coordination in the institutional arrangements of the RFEPCT Expansion Plan in the vertical (intergovernmental), horizontal (intragovernmental), territorial and participatory dimensions. The main results show that the participatory dimension was marked by the performance of the Department of Technological Education (SETEC) of the Ministry of Education (MEC) as an articulator of seminars, conferences and forums, which had the presence of sectorial actors and parliamentarians in the debates and definition of policy priorities. In the vertical dimension, the (SETEC) is observed in the coordination of the processes of adherence to the policy, and the role of the federal government is highlighted, as the action of the municipalities takes place in a marginal way. In intersectoriality, despite the federal government’s intentions to integrate the programs and policies of different ministries into the RFEPCT’s expansion plan, what was observed was the overlapping of actions, without a coordinated action of these policies. Finally, the territorial dimension considered regional development policies and prioritized meeting local productive arrangements (APLs), the polo cities and the Citizenship Territories, in the definition of the municipalities that would receive the new campuses, defining the territories as the plan’s execution unit.